Pengaruh Media Musik Klasik terhadap Tingkat Stres pada Mahasiswa Tingkat Akhir Jurusan Promkes Poltekkes Kaltim - Muftia Ade Maharani; Yona Palin T; Emelia Tonapa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Background: According to age group characteristics, young adults in Indonesia aged between 15 and 24 years have higher rates of depression (2%). Depression is higher among females (2.8%) than males (1.1%). East Kalimantan's rate of depressive disorder (2.2%) is 2nd nationally. One of the activities that make students stressful in their academic work is making a thesis. Students who experience academic stress can benefit from music therapy. Purpose: The purpose of this study was to determine the effect of classical music media on stress levels in final year students majoring in health promotion at the poltekkes kemenkes east Kalimantan. Methods: The research was conducted on April 23, 2025. The population and sample size were 35 respondents. The type of research used is pre-experimental with a one-group pretest- posttest design. Results: The results of the analysis showed that 30 respondents were female and 5 were male. Stress levels before classical music therapy ware almost half moderate stress (45.7%) while after being given classical music therapy most of them decreased to normal (71.4%). The results of the stress level data test using the Wilcoxon test (T-Test) obtained a P-value = 0.000, because the P-value < (α = 0.05), then H0 is rejected and Ha is accepted. Conclusion: There is an effect of classical music media on stress levels in final year students majoring in health promotion at the poltekkes kemenkes east Kalimantan.